La Plaque Console Du Radius : Une Alternative Dans L’ostéosynthèse Des Fractures De L’extrémité Supérieure De L’humérus ? - A, Walla; A, Abalo; YE, James; B, Bakriga; T, Towoezim; NK, Kombaté; K, Amakoutou; AM, Dossim (European Scientific Journal, ESJ, 2016)
The aim of this study was to report the results of our experience in the treatment of proximal fractures with distal radius plate. This prospective study was conducted between January 2010 and December 2014. It took into account patients with a body mass index (BMI) not more than 25 kg/m2 in which the indication of conservative surgical treatment was decided and who did not have enough financial means to fulfill the required implants. The Neer classification was used to characterize fracture. To assess treatment outcomes, we used UCLA (University of California in Los Angeles) slightly modified score. There were 17 patients including 10 men and 7 women with a mean age of 32 years. According to Neer classification, six patients (35,29%) had stage I lesions, 5 others (29,42%) stage II and 6 patients (35,29%), stage III. There was no open fracture. There were three cases (17, 66%) of fracture-dislocations with one posterior variety. The average time of care was 13, 7 days (with a range of 2 to 29 days). The average time of healing was 117, 4 days with extremes of 81 days and 4 months 10 days. All patients were consolidated. The results at a mean of 15.31 months revealed excellent results in 29.41% and 29.41% poor results. In young patients whose treatment should be as conservative as possible, the distal radius plate could be an alternative if patient BMI does not exceed 25 kg/m2 and the epiphyseal screws are not too long. In case of comminuted fracture, it seems more desirable to postpone the osteosynthesis of weeks. However, only other subsequent studies on larger samples and longer followup, may lead to some conclusions about the usefulness of the distal radius plate in these lesions.